Über die heckesche Zetafunktion des reel-quadratischen Zahlkörpers. I - Matuliauskas, A. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. Матуляускас. О ζ-функции Гекке вещественного квадратичного поля. IA. Matuliauskas. Apie realaus kvadratinio skaičių kūno Hekės ζ-funkciją. I